Pregnant Women's Quality of life during the Covid-19 Pandemic: An Example from Makassar, Indonesia : Kualitas Hidup Ibu Hamil di Masa Pandemi Covid-19: Studi Kasus Kota Makassar, Indonesia - Citrakesumasari; Rachmat Muhammad; Rahmatsah Said; Elvita Bellani; Sitti Andriani Anwar (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2022)
Pregnancy is a period of considerable mental and physical change which affects quality of life, even without any complications. during the Covid-19 pandemic, there were limited report on pregnancy care. This study aims to investigate the effect of Covid-19 infection on the physical and psychological health status of pregnant women. It also provide data on the potential risk of food insecurity, which still exist particularly in developing countries. 65 pregnant women participated in this study, meanwhile, the survey was transferred and shared on Google during the online review stage for one month using convenience sampling (non-probability sampling). Furthermore, this study was carried out using a cross-sectional design, while the data were collected via two questionnaires, namely World health Organization Quality of Life (WHOQOL-BREF) and Maternal Consumption behavior during pregnancy. The results showed that the respondents have good quality of life (56.9%) as stated in WHOQOL-BREF. The majority of the respondent are in good category in terms of physical (90.8%), psychological (70.8%), social relationship (61.5%) and environmental domain (90.8%). However, 6% were in the bad category in relation to general life quality. Regarding the perceived health status, approximately half of the respondent were satisfied with individual health during the pandemic, while 3.1% and 10.6% were very satisfied and unsatisfied respectively. It is recommended the pregnant women to be screened for household food security status and life quality during main prenatal care approach that includes policymaking, resource allocation, and proper service delivery with the goal of guaranteeing pregnant women's access to a variety of high-quality meals and good life quality.